2020
DOI: 10.1186/s13071-020-04031-3
|View full text |Cite
|
Sign up to set email alerts
|

Ability of near-infrared spectroscopy and chemometrics to predict the age of mosquitoes reared under different conditions

Abstract: Background: Practical, field-ready age-grading tools for mosquito vectors of disease are urgently needed because of the impact that daily survival has on vectorial capacity. Previous studies have shown that near-infrared spectroscopy (NIRS), in combination with chemometrics and predictive modeling, can forecast the age of laboratory-reared mosquitoes with moderate to high accuracy. It remains unclear whether the technique has utility for identifying shifts in the age structure of wild-caught mosquitoes. Here w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, when NIRS was used to predict Ae. albopictus mosquitoes reared from wild pupae using a model developed from laboratory-reared mosquitoes, young and old mosquitoes could not be differentiated [83]. Based on the authors' description of their experimental design, the inability to predict the age of mosquitoes collected from wild pupae is most likely due to a weak predictive model that failed to capture the heterogeneity of the wild population including variation in the larval diet.…”
Section: -1730mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when NIRS was used to predict Ae. albopictus mosquitoes reared from wild pupae using a model developed from laboratory-reared mosquitoes, young and old mosquitoes could not be differentiated [83]. Based on the authors' description of their experimental design, the inability to predict the age of mosquitoes collected from wild pupae is most likely due to a weak predictive model that failed to capture the heterogeneity of the wild population including variation in the larval diet.…”
Section: -1730mentioning
confidence: 99%
“…Based on the authors' description of their experimental design, the inability to predict the age of mosquitoes collected from wild pupae is most likely due to a weak predictive model that failed to capture the heterogeneity of the wild population including variation in the larval diet. Alternatively, the small sample size used for model development was not robust [83]. A previous study indicated that Anopheles mosquitoes reared from wild pupae could be predicted accurately if models were developed from a similar mosquito population and neither species type nor exposure to pyrethroids affected the ability of NIRS to predict their age [76].…”
Section: -1730mentioning
confidence: 99%
“…The premise that every species has a unique chemical composition allows the advantageous use of FTIR spectroscopy for taxonomic purposes. Near-infrared spectroscopy (NIRS) was used to quickly identify the age of the Aedes albopictus mosquito population in order to avoid a potential epidemic of, e.g., diseases such as dengue and Zika [ 1 ]. An attenuated total reflection–Fourier-transform infrared (ATR-FTIR) spectrometer for acquiring high-resolution mid-infrared (MIR) spectra (4000 cm −1 to 400 cm −1 ) was used to discriminate blood samples originating from a common vertebrate host, collected from the malaria vector, Anopheles arabiensis , and this method avoided the required molecular techniques [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared spectroscopy (NIRS) is a rapid, high-throughput and relatively inexpensive technique that has been used for a decade to predict the species, age and infection status of certain disease vectors, such as Anopheles and Aedes mosquitoes [ 3 5 ]. Many of these different studies used laboratory or field mosquitoes to assess the accuracy of NIRS to differentiate between Anopheles species [ 3 , 4 ], mosquito age [ 3 , 6 ] and Anopheles infection status using Plasmodium culture [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these different studies used laboratory or field mosquitoes to assess the accuracy of NIRS to differentiate between Anopheles species [ 3 , 4 ], mosquito age [ 3 , 6 ] and Anopheles infection status using Plasmodium culture [ 7 , 8 ]. The reliability of the method for application in entomological surveillance studies using wild mosquitoes is less clear, with models trained on laboratory-reared mosquitoes being unable to accurately predict the infection status or age of field mosquitoes [ 5 , 9 ]. Further work is therefore required to verify these results, and it may be necessary to calibrate NIRS models with greater numbers of wild-caught mosquitoes.…”
Section: Introductionmentioning
confidence: 99%